Relação do perfil proteômico diferencial do plasma seminal de búfalos com a longevidade espermática pós descongelamento - Patrícia de Alencar Auler (2018)
This study aimed to evaluate proteomic profile of seminal plasma of buffaloes (Bubalus bubalis) related to sperm resistance to the freezing-thawing process. Therefore, 118 ejaculates of 13 buffalo bulls were submitted to sperm freezing process. Prior to processing, an aliquot of each ejaculate was centrifugated and the seminal plasma recovered for posterior proteomic analyses. Sperm resistance to the freezingthawing process was evaluated through motility and kinetic parameters, provided by CASA (Computer Assisted Sperm Analysis), at different moments: just before cooling (PR), just before freezing (PC) and after thawing at five (PD_T5), 60 (PD_T60), 120 (PD_T120) and 180 (PD_T180) minutes. Differences in proteomic profile were evaluated in difference in-gel electrophoresis (DIGE). For all analyses p ≤ 0.05 was considered. Inter and intra-individual variations in post-thaw sperm longevity were observed with the greatest variability presented between ejaculates from the same semen donor. Based on the decline of the total motility between PR and PD_T180, the ejaculates that presented the highest (group of high sperm resistance – HR, n = 21) and the lowest (group of low sperm resistance – LR, n = 19) sperm resistance to freezing-thawing were selected. The HR and LR ejaculates presented similar sperm characteristics before freezing, except for velocity parameters (VCL, VSL, VAP), which were higher in the HR group (p ≤ 0.05). Just after thawing and during the post-thaw incubation period, the HR ejaculates maintained higher velocity (VCL, VSL, VAP) and presented higher values of total motility and rapid cells at all the evaluation times (p ≤ 0.05). After thawing, especially at the end of the incubation period (120 and/or 180 minutes post-thaw), the HR group also presented higher values of ALH, STR, BCF and LIN (p ≤ 0.05). Nine HR and eight LR ejaculates were selected to proteomic analysis. Thirtyfour spots showed differential intensity in HR and LR pools of seminal plasma, of which 30 were presented in higher intensity in HR group and four in LR group (p ≤ 0.05). Among the spots with higher intensity in HR group, 14 presented molecular weight between 33 and 41 kDa and isoelectric point of 4.2 to 4.9, respectively. These spots represented 41.2% of the total number of spots with differential intensity and 43.8% of total relative intensity. Of those 14 spots, 12 were identified by MALDITOF/TOF mass spectrometry as Clusterins. Furthermore, 14-3-3 zeta/delta protein was identified as more abundant in LR group. It was concluded that buffalo ejaculates had great variability in sperm resistance to the freezing-thawing process, which was characterized by higher post-thaw sperm survival and specially longevity. Furthermore, HR e LR ejaculates presented differences in proteomic profile of seminal plasma with higher abundance of Clusterin in the seminal plasma of HR ejaculates.